2021
DOI: 10.1186/s12885-020-07757-6
|View full text |Cite
|
Sign up to set email alerts
|

The NeST (Neoadjuvant systemic therapy in breast cancer) study: National Practice Questionnaire of United Kingdom multi-disciplinary decision making

Abstract: Background Neoadjuvant systemic therapy (NST) is increasingly used in the treatment of breast cancer, yet it is clear that there is significant geographical variation in its use in the UK. This study aimed to examine stated practice across UK breast units, in terms of indications for use, radiological monitoring, pathological reporting of treatment response, and post-treatment surgical management. Methods Multidisciplinary teams (MDTs) from all UK … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…The perception that all breast tissue initially involved by the tumor must be excised at the time of surgery may lead to unnecessary mastectomies in this setting. 13,14 Although guidelines such as those published by the St. Gallen International Expert Consensus advise that resection of the entire tumor bed after neoadjuvant treatment is not necessary, 15 practice remains highly variable. In a recent survey of all multidisciplinary teams from breast units in the United Kingdom, 26% of centers reported resection of the original tumor footprint, regardless of clinical and radiologic responses.…”
Section: + ++++ + +++ + + +++ +++ + + + + + + +++ +++ + + + + ++ ++ ++ + + + + + + + + + ++ + + ++ + + + + + ++ + ++ + ++ + + + + + ++ + mentioning
confidence: 99%
See 1 more Smart Citation
“…The perception that all breast tissue initially involved by the tumor must be excised at the time of surgery may lead to unnecessary mastectomies in this setting. 13,14 Although guidelines such as those published by the St. Gallen International Expert Consensus advise that resection of the entire tumor bed after neoadjuvant treatment is not necessary, 15 practice remains highly variable. In a recent survey of all multidisciplinary teams from breast units in the United Kingdom, 26% of centers reported resection of the original tumor footprint, regardless of clinical and radiologic responses.…”
Section: + ++++ + +++ + + +++ +++ + + + + + + +++ +++ + + + + ++ ++ ++ + + + + + + + + + ++ + + ++ + + + + + ++ + ++ + ++ + + + + + ++ + mentioning
confidence: 99%
“…In a recent survey of all multidisciplinary teams from breast units in the United Kingdom, 26% of centers reported resection of the original tumor footprint, regardless of clinical and radiologic responses. 13 Similarly, in the Neoadjuvant Lapatinib and/or Trastuzumab Treatment Optimisation (NeoALLTO) trial of neoadjuvant treatment for HER2+ cancers, despite dramatic improvements in pCR rates with dual HER2 blockade, BCS rates did not increase, and the use of BCS remained most frequent among those who were deemed BCSe at diagnosis. 16 However, data from past studies, including a retrospective study of 509 consecutive patients with T1-3N0-2 cancers treated in prospective trials of chemotherapy from 1998 to 2005, have demonstrated the safety of limiting resection to residual viable tumor.…”
Section: + ++++ + +++ + + +++ +++ + + + + + + +++ +++ + + + + ++ ++ ++ + + + + + + + + + ++ + + ++ + + + + + ++ + ++ + ++ + + + + + ++ + mentioning
confidence: 99%
“…A survey of British breast cancer teams reported that 74% of centers practice response-adapted surgery, whereas 26% stated that they resect the original tumor footprint [25]. The 2017 St. Gallen consensus panel voted on de-escalation of surgery after NST: 82% of panelists voted that surgical resection should include only the post-NST extent of the tumor, and only 14% voted that the original (pretreatment) tumor bed needs to be excised [26].…”
Section: Bcs and Margins After Nstmentioning
confidence: 99%
“…A common indication for NET is to convert mastectomy to BCS, although this is achieved at lower rates than NAC [25]. Semiglazov et al reported a phase 2 trial of NET compared with NAC in 239 postmenopausal patients with ER-positive breast cancer, all ineligible for BCS at diagnosis.…”
Section: Neoadjuvant Endocrine Therapy and Surgery Of The Breastmentioning
confidence: 99%
“…Neoadjuvant systemic therapy (NeST) is routinely used to treat breast cancer, with significant geographical variation in its use across different countries ( 1 , 2 ). When introduced, NeST was used mostly for the treatment of patients with locally advanced or inoperable breast cancer aiming to reduce the tumor size, enabling post-therapy breast-conservation surgery.…”
Section: Introductionmentioning
confidence: 99%